Identifikasi Sebaran Gumuk Jember dan Kaitannya dengan Perubahan Vegetasi Menggunakan Teknologi Penginderaan Jauh - Elsa Shaffaros Ahmad (Fakultas Teknik, 2023)
Mound in Jember Regency was formed by the lava flow of Mount Raung which lasted for several centuries. The main elements of dune are rocks consisting of plate stone, sand and foundation stone. Time pass by, the mounds in Kabupaten Jember have been steadily diminishing, accompanied by changes in the level of greenery in the region. This study aims to determine the distribution of the mounds, changes in the vegetation index, and the correlation between the mounds and vegetation changes. The research was conducted in the northern part of Kabupaten Jember, encompassing eight sub-districts within the region. Qualitative data for this study consisted of documentation and coordinate data for the mounds in Kabupaten Jember, quantitative data was obtained from satellite imagery in the form of raster data and administrative shapefiles (shp) for Kabupaten Jember. The data sources were obtained from the United States Geological Survey (USGS) EROS Data Center, specifically using Landsat 8 Path 117/Row 066 and SRTM data. The research findings, using 2014 SRTM data, identified a total of 595 mounds scattered across the eight sub-districts. The vegetation index in Kabupaten Jember showed a decrease of 16% from 2014 to 2022. This decline in the vegetation index can be attributed to infrastructure development, commercial areas, housing, and mining processes. Based on observations, the mounds were categorized into three types: mounds in active mining areas, mounds in former mining areas, and intact mounds. The use of modified SRTM data helped in identifying the presence of these mounds. Changes in vegetation, based on NDVI analysis from 2014 to 2022, showed a decrease in vegetation density by 16%. Mounds in active mining areas tended to have reduced vegetation, whereas mounds with denser vegetation exhibited more stable vegetation indices.
Reuploud Repository hasyim Mei 2026 Approved by Teddy
Keywords: Gumuk; NDVI; Landsat 8; SRTM